2011
DOI: 10.1002/etc.683
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial ecotoxicity of short aliphatic protic ionic liquids

Abstract: A study of the ecotoxicity of different short aliphatic protic ionic liquids (PILs) on terrestrial organisms was conducted. Tests performed within the present study include those assessing the effects of PILs on soil microbial functions (carbon and nitrogen mineralization) and terrestrial plants. The results show that the nominal lowest-observed-adverse-effect concentration (LOAEC) values were 5,000 mg/kg (dry soil) for the plant test in two species (Lolium perenne, Allium cepa), 1,000 mg/kg (dry soil) for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 37 publications
0
27
0
4
Order By: Relevance
“…Structures of the used reactants and the obtained PILs are presented in Table 1. These liquids were chosen since they are in liquid state at room temperature, they have low toxicity because their simple structure favors biodegradability 32,33 , and their capability for being adsorbed onto the metal surface due to the presence of the oxygen and nitrogen atoms 6,34 , that can improve both lubrication and corrosion performance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structures of the used reactants and the obtained PILs are presented in Table 1. These liquids were chosen since they are in liquid state at room temperature, they have low toxicity because their simple structure favors biodegradability 32,33 , and their capability for being adsorbed onto the metal surface due to the presence of the oxygen and nitrogen atoms 6,34 , that can improve both lubrication and corrosion performance.…”
Section: Methodsmentioning
confidence: 99%
“…Other authors also observed similar performances between imidazoliumbased ionic liquids and conventional cutting fluids for micro-milling application 30 . In addition, an advantage of using protic ionic liquids as simple as the ones used in this work is their biodegradability and low ecotoxicity, compared to oils and ionic liquids with more complex structures, which eases their disposal 32,33 .…”
Section: Lubricant Fluidmentioning
confidence: 99%
“…These results show the influence of ionic liquid composition and polarity on the miscibility with the epoxy matrix, when compared with previously described epoxy resin+APIL materials. Thus, while the shortalkyl chain 1-ethyl-3-methylimidazolium tetrafluoroborate concentrated in small (2-3 μm mean diameter) cavities [30], the less polar, longer-alkyl chain 1-octyl-3-methylimidazolium tetrafluoroborate APIL was miscible with the epoxy matrix, showing a homogeneous distribution within it [33,39,43]. The PIL tricationic tricarboxylate DCi, presents a higher polarity than any of the imidazolium APILs, thus it could be concluded that the more polar is the ionic liquid phase, the less miscible with the epoxy matrix, leading to the formation of larger cavities containing the ionic liquid phase.…”
Section: Study Of Pil Distribution In the Epoxymentioning
confidence: 99%
“…Several research groups are currently working in the study of halogen-free ILs which could substitute the conventional ones [30,41,42]. We have recently developed new lubricants and additives based on protic ionic liquids (PILs), in particular protic ammonium carboxylate salts, some of which show outstanding lubricating behaviour [25,[41][42][43]. The main objective of the present study is to develop new epoxy resin protic ionic liquid hybrid materials in a simple way, and to determine the effect of the additive on the properties and tribological performance of the polymer, in particular, to prevent the severe surface damage and high friction coefficients of brittle epoxy resin materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation